2006
DOI: 10.1002/nvsm.282
|View full text |Cite
|
Sign up to set email alerts
|

‘Escaping to the gallery’: understanding the motivations of visitors to galleries

Abstract: *Whilst market research and academic studies by sociologists have identified the personal and socio-cultural factors that influence visits to galleries, there has been less attention to the area of motivational research. Understanding motivations is important as it reveals the underlying reasons why visitors choose to participate in specific leisure activities. This paper focuses on the motivations of two groups of visitors at events at an art gallery. A pretested motivational scale built around three factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 36 publications
4
53
1
1
Order By: Relevance
“…Bergadaà and Nyeck's work confirmed earlier research into consumer behaviour, which found that the most cited motivations for a leisure experience were pleasure and escapism (Unger and Kernan 1983). This finding is supported by Slater (2007), whose research into the motivations of visitors to art galleries also revealed escapism as the core motivator, challenging the widely acknowledged view in the museums and galleries sectors that learning was the primary motivation. But it is contested by other research into consumer behaviour in arts and culture, which delineates shared experience and social engagement as dominant motivators (Arai and Pedlar 2003;Bourgeon-Renault 2000).…”
Section: Understanding Audience Motivationsupporting
confidence: 63%
See 2 more Smart Citations
“…Bergadaà and Nyeck's work confirmed earlier research into consumer behaviour, which found that the most cited motivations for a leisure experience were pleasure and escapism (Unger and Kernan 1983). This finding is supported by Slater (2007), whose research into the motivations of visitors to art galleries also revealed escapism as the core motivator, challenging the widely acknowledged view in the museums and galleries sectors that learning was the primary motivation. But it is contested by other research into consumer behaviour in arts and culture, which delineates shared experience and social engagement as dominant motivators (Arai and Pedlar 2003;Bourgeon-Renault 2000).…”
Section: Understanding Audience Motivationsupporting
confidence: 63%
“…But this approach circumvents the possibility that people with similar values can be driven by different motivations on different occasions (Slater 2007); and even among proponents of values research, there is a lack of consensus about how values can most effectively be measured. One popular approach is laddering, whereby respondents' values are mapped hierarchically through probes, which delve behind their actions and attitudes to find core values or motives (Thyne 2001).…”
Section: Understanding Audience Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with intrinsic motivation, for which engagement in the act is sufficient in itself (Alexandris, Tsorbatzoudis, & Grouios, 2002). Visitors' cognitive learning, reflective and recreational motivation is associated with their visiting experience and reasons associated with their museum visit (Falk, 2013;Prentice, 2001;Slater, 2007). Taheri et al (2014) identified recreational and reflective motivation to determine museum visitors' level of engagement.…”
Section: Motivation In Literary Museum Contextmentioning
confidence: 99%
“…The recent researches on museum consumer behavior reveal that museum visits are not anymore a simple informative cultural visits, but they are experiences (Falk and Dierking, 1992;Prentice et all., 1997;Kawashima, 1998;Goulding, 1999;Rowley, 1999;Goulding, 2000;Thyne, 2001;Bollo, 2004;Hume et all., 2006;Rojas and Camarero, 2006;Slater, 2007;Bifulco and Ilario, 2007;McCarthy and Ciolfi, 2008;Chan, 2009). The concept of experience becomes a key leading to consumer satisfaction.…”
Section: Museum Experiencesmentioning
confidence: 99%